Time to initiation of antenatal care visit and its predictors among reproductive age women in Ethiopia: Gompertz inverse Gaussian shared frailty model - Belay, Daniel Gashaneh; Alemu, Melaku Birhanu; Aragaw, Fantu Mamo; Asratie, Melaku Hunie (Frontiers in Global Women's Health, 2023)
Background: Early initiation of antenatal care (ANC) is essential for the early detection of pregnancy-related problems and unfavorable pregnancy outcomes. However, a significant number of mothers are not initiating ANC as per the recommended time. Therefore, this study aimed to determine the median time of antenatal care initiation and its predictors among reproductive-age women in Ethiopia.Methods: We used the Ethiopian Demographic and Health Survey (EDHS) 2016 data set. The proportional hazard assumption was assessed using Schoenfeld residual test, and Log-Log plot.A life table was used to determine the median survival time (time of ANC initiation). The Gompertz inverse Gaussian shared frailty model was the best-fitted model to identify the predictors for the early initiation of ANC booking. Finally, the Adjusted Hazard Ratio (AHR) with a 95% confidence interval (CI) was used to determine the significance of predictors.Results: A total of 7501 reproductive-aged women gave recent birth in the last 5 years preceding the survey. Nearly three in five women 61.95% (95%CI: 60.85%, 63.04%) booked their first ANC visit with a median time of 4.4 months. Women who attended primary education